TEACHERS' STRATEGIES IN FOSTERING STUDENTS' INTEREST IN LEARNING ARABIC LANGUAGE AT SMP MUHAMMADIYAH PLUS SALATIGA - Firda, Tsany Amaliya; Al Qibtie, Nada Marya; Nashiruddin; Guntur Cahyono (Yayasan Amanah Nur Aman, 2025)
This study aims to explore the strategies used by teachers to foster students’ interest in learning Arabic at SMP Muhammadiyah Plus Salatiga. The research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. Three different learning strategies were implemented based on grade levels: roleplay activities in Grade VII, the talking stick method in Grade VIII, and the use of Kahoot as an evaluation tool in Grade IX. The findings reveal that each learning strategy effectively increases students' engagement and interest in learning Arabic. Roleplay helps students develop confidence and improve speaking skills by actively participating in simulated conversations. The talking stick method promotes focus and participation by encouraging spontaneous responses during class discussions. Meanwhile, Kahoot provides a modern and interactive evaluation platform that motivates students through its competitive and game-based format. Overall, this study highlights the importance of using varied and interactive teaching strategies to enhance students’ motivation and learning outcomes in Arabic language classes. The results also emphasize the teacher's role as a facilitator in creating a conducive and enjoyable learning environment.